Transperitoneal laparoscopic approach for retroperitoneal tumors in adults - Minetti, Ángel M.; Pitaco, Ignacio; Gómez, Eduardo; Martínez, Esteban (Revista Argentina de Cirugía, 2021)
Background: The retroperitoneal space contains organs, blood vessels, a rich network of lymphatic nodes, abundant connective tissue and neural tissue, and different types of embryonic remnants. Retroperitoneal tumors originate in these tissues and conventionally do not include those located in organs in the retroperitoneal space (kidneys, adrenal glands or pancreas). Material and methods: Patients undergoing retroperitoneal tumors by transperitoneal laparoscopic approach between 2008 and 2019 were included. Those cases with tumors with suspected malignancy, tumor recurrence, need for multivisceral resection and those < 18 years were excluded. Results: 9 patients were included; 55% (n = 5) were men; mean age was 42.3 years (19-62); body mass index (BMI) 28.3 kg/m2 (25-35.8). The tumor was located was below the third part of the duodenum in 1 patient, and in the inframesocolic space in 8: 3 on the right, 3 on the left, 2 intercavo-aortic tumors, and 1 para-aortic lesion. The mean size of the lesions was 13.05 cm (4-29 cm). Mean operative time was 184.4 minutes (110-330 min). Length of hospital stay was 3.33 days (2-6 d). Conversion: 1 (11.1%). The pathology examination reported well-differentiated liposarcoma (lipoma-like lesion) (n = 2); cystic lymphangioma (n = 2); hemangioma (n = 1); functioning paraganglioma (n = 1); schwannoma (n = 1); simple serous cyst (n = 1); and adipose tissue fibrosis (n = 1). Long-term follow-up was 30 months (12-72 months).